2023
DOI: 10.3390/ijerph20042887
|View full text |Cite
|
Sign up to set email alerts
|

Be Prosocial My Friend: The Social Disconnection Model of Perfectionism in Adolescents Immersed in Competitive Sport

Abstract: The aim of the present study is to explore the relationships between cognitive–behavioral patterns of perfectionism in the context of competitive sport and both prosociality and aggressiveness in a sample of adolescents competing in federated sports. A cross-sectional and non-randomized study was designed using a selective methodology on a sample of adolescents (N = 234) competing in federated sports. Scales to assess aggressiveness, perfectionism, prosocial behavior, and competitiveness were administrated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…We have found significant differences in social skills by gender: Men's perceptions of both aggressiveness and pretentiousness and haughtiness were higher than women's. On the other hand, as mentioned before, other authors suggest that the abilities developed within the PE and sport environment (e.g., empathy, altruistic behaviors, and forgiveness) will be transferred to other life scenarios, protecting the students from inappropriate social behaviors and social violence in other life contexts (Rodríguez-Franco et al, 2023). Related to this topic, Ortega Vila et al (2019) found that students who participated in team sports competitions specifically created to be of an educational nature showed more sporting attitudes and personal and social factors than those who did not participate in those competitions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have found significant differences in social skills by gender: Men's perceptions of both aggressiveness and pretentiousness and haughtiness were higher than women's. On the other hand, as mentioned before, other authors suggest that the abilities developed within the PE and sport environment (e.g., empathy, altruistic behaviors, and forgiveness) will be transferred to other life scenarios, protecting the students from inappropriate social behaviors and social violence in other life contexts (Rodríguez-Franco et al, 2023). Related to this topic, Ortega Vila et al (2019) found that students who participated in team sports competitions specifically created to be of an educational nature showed more sporting attitudes and personal and social factors than those who did not participate in those competitions.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, these abilities, which are developed within the PE and sport environment (e.g., empathy, altruistic behaviors, and forgiveness), could be transferred to other life scenarios (Turnnidge et al, 2014). PE and sport may help to both fostering social abilities in anticipation of and protecting antisocial behaviors and social violence (Rodríguez-Franco et al, 2023) and to promote children's PA and develop lifelong exercise habits.…”
Section: Self-determination Theory (Sdt) and Social Skills In Pe Envi...mentioning
confidence: 99%
“…Several theoretical perspectives, such as expectancy-value theory ( Wigfield and Eccles, 2000 ), goal theory ( Elliot and McGregor, 2001 ), and SDT, have been used to examine students’ social skills ( Ryan and Deci, 2017 ), but is SDT the one that has been widely used to look at motivation in both educational and PE settings, what is the context of this research, so this is why we chose it as our conceptual framework. Some academics have suggested using PE and sport environments to help young people improve their social skills (e.g., communicational skills, value-based expressions) in terms of developmental objectives ( Anderson-Butcher and Bates, 2018 ; Nascimento Junior et al, 2021 ) and others also suggest that these abilities will transfer to other life scenarios if they are developed within the environment of PE and sport (e.g., empathy, altruistic behaviors, forgiveness), that fosters social abilities in anticipation ( Turnnidge et al, 2014 ) and protect of antisocial behaviors and social violence ( Rodríguez-Franco et al, 2023 ) when the competitive sport increases. Since among the postulates of the Self-Determination Theory is the promulgation of the relation of motivational constructs and needs to a person’s development and global functioning, including the development of global-life competencies such as social skills ( Ryan and Deci, 2017 ), in this research we wanted to analyzed the relationships between these competencies and Self-Determination Theory main variables in our study context, a sample of disadvantaged Chinese students from rural areas attending PE lessons.…”
Section: Introductionmentioning
confidence: 99%